A cross-sectional epidemiological study reveals a strong link between tuberculosis, social vulnerability, and HIV-Tuberculosis co-infection in Central Mozambique (Research, Society and Development, 2025)
This study aims to describe the socio-demographic characteristics of TB patients in Buzi, assess the clinical features, including TB type and HIV co-infection, and review TB control strategies in the district. Tuberculosis (TB) remains a significant public health challenge in Mozambique, especially in Búzi. This study characterized the epidemiological profile of TB patients treated in Búzi district, between 2020 and 2022. A descriptive, cross-sectional study was conducted using secondary data from patient registers at four public health units: Búzi Rural Hospital and the health centers of Bandua, Estaquinha, and Barada. The sample included all patients aged 18 or older with a confirmed TB diagnosis. Data were analyzed using SPSS version 20 to generate descriptive statistics and identify patterns of TB-HIV co-infection. A total of 1,065 TB cases were identified, with 53% of patients being female and 52.9% aged between 36 and 60 years. A significant proportion had no formal education and were either unemployed or engaged in domestic occupations. TB-HIV co-infection was found in 28.1% of cases. Treatment completion was reported in 77.8% of patients, while 2.5% died. TB-HIV co-infection was significantly associated with sex, age group, place of residence, and TB type. The study highlights the strong association between TB, social vulnerability, and HIV co-infection in Búzi. Strengthening access to diagnostics, expanding treatment coverage, and implementing integrated care strategies are essential to improving outcomes in similar rural contexts.